Modernização, instituições e revolução: o caso iraniano (1953-1979) - Munareto, Camila Hirt (2019)
The present research aims to contribute to a better understanding of the challenges posed by modernization to political development and its relations with the revolutionary processes. The object of study is the Islamic Republic of Iran and the research seeks to understand if "the iranian revolution of 1979 is a reaction of the traditional elites to the process of modernization that begun with the Shah's government in 1953. How and why?". To awnser this question, the research will use the path dependence as a theoretical-methodological instrument, emphasizing the existence of political legacies and its impacts on subsequent political choices. So, the process of Iranian modernization and political development will be analysed from two critical moments and the institutional trajectory established between them: (i) the coup of 1953 and (ii) the Islamic Revolution of 1979. The hypothesis adopted is that the Islamic Revolution consists in a reaction of the traditional elites to the process of modernization initiated in 1953. The changes promoted by the coup of State began a new political trajectory in Iran and promoted not only rapid economic growth, but also changes in the behavior patterns of society. In contrast, especially since the White Revolution of 1963, traditional elites were systematically cut off from decision-making spheres, and political institutions lost their autonomy as an instance of modulation of social demands. This discrepancy between modernization and political development established a scenario of political instability, in which the traditional elites could act. With a narrative capable of providing security and certainty to Iranian society in times of rapid change and dismantling of traditional values and attitudes, traditional elites managed to channel the social frustration of modernization and led the Islamic Revolution of 1979. The aim of this study is to understand the challenges posed by modernization to political stability and under what conditions political instability favors the development of a revolutionary rupture.